Integrasi Pembelajaran Active Learning dan Internet-Based Learning dalam Meningkatkan Keaktifan dan Kreativitas Belajar - Effendi, Mukhlison (Nadwa, 2013)
The learning process in higher education can use constructivist learning strategies for activeness and creativity of students. This study aimed to des-cribe the integration of active learning and internet-based learning and to explain the factors supporting and inhibiting. From the observation data, in-terviews and documentation of the 31 students of the Department of Teacher Education for Islamic Primary Education (PGMI) and the lecturer of STAIN Ponorogo can be seen that the integration of active learning and Internet-based learning can enhance the activeness and creativity of student learning in the course. Factors supporting this result are the application of learning strategies, giving clear guidance, student learning motivation high and the availability of learning facilities and infrastructure. The factors that inhibit is the limited time, the dominance of smart students and unpreparedness of students receiving new material.